Effects of storage conditions on milk powder properties - A.E. Ryabova; V.K. Semipyatny; A.G. Galstyan (Journal of Dairy Science, 2023)
ABSTRACT: Studies on the storage stability of milk powder are currently fragmented and mainly affect only the area of above-zero temperatures. At the same time, there are no studies that consider the load factor when milk powder is stored in bags on a pallet. The purpose of this study was to identify the influence of various factors of industrial storage (temperature, height or layer number, and time) on the change in quality and technological properties of powdered dairy products. We placed skim milk powder (SMP) and whole milk powder (WMP) in 10 × 14 × 2 cm resealable plastic bags on a model stand simulating an industrial layout on pallets. The samples were stored for 18 mo at temperatures −30 ± 1°C, 6 ± 1°C, and 25 ± 3°C and 40 to 80% relative humidity. Samples from the control (0), 5, and 10 (lower) layers of pallets were selected for analysis on 0, 3, 6, 9, 12, 15, and 18 mo of storage for each of the temperatures. As a result, we did not detect any changes in the storage process for water activity and mass fraction of moisture. The particle size distribution of all the SMP and WMP samples changed over time. The greatest changes were observed in the WMP samples placed on the 10th layer of pallets at 25 ± 3°C, from 0 to 18 mo of storage, the mean particle size (D[4,3]) increased from 120 to 258 μm (90% of all sample particle sizes ranging from 209 to 559 μm). We found significant clumping in the WMP samples (lumps up to 5 cm), correlating with the layer and storage time. The contact angle of the samples increased from 17° (SMP) and 53° (WMP) to 40° and 71°, respectively. The insolubility index and titratable acidity did not change only in the SMP samples stored with no load applied at −30 ± 1°C and 6 ± 1°C. The heat stability of all samples stored at 25 ± 3°C showed the lowest values. The data obtained allowed us to rank the factors as “layer – time – temperature.” Only the temperature of 25 ± 3°C caused critical changes in the product properties. Thus, the possibility of industrial storage of the product for up to 15 mo over the entire temperature range is confirmed.